Seismic Performance Evaluation of an Existing 3-Story RCC Building Using Pushover Analysis - Shrestha, Rekha; Maharjan, Salina (Mid-West University Journal of Engineering & Innovation, 2025)
This study presents a seismic performance evaluation of an existing 3- story reinforced concrete (RCC) building located in Kathmandu using nonlinear static (pushover) analysis in ETABS. The building was originally designed according to IS 1893:2002, and the assessment is carried out in compliance with NBC 105:2020 to evaluate whether the building satisfies the requirements of the updated code. Actual structural details, material properties and hinge assignments are incorporated to accurately model the building's behavior under lateral loading. The performance point is determined using FEMA 440 Equivalent Linearization procedures, and the building’s capacity is assessed through capacity curves. The analysis reveals that the existing structure satisfies the Immediate Occupancy (IO) performance level in the X-direction and Life Safety (LS) in the Y-direction, indicating acceptable performance under design-level seismic forces. A modified model with an additional one story shows a decrease in base shear capacity and an increase in displacement, with performance levels reducing to LS in the X-direction and Collapse Prevention (CP) in the Y-direction. These findings suggest that while vertical extension is structurally feasible, it compromises the seismic performance, particularly in the Y-direction. The study emphasizes the need for careful evaluation and retrofitting strategies when considering structural modifications in seismically active regions.